Using Project Work to Develop and Practice Writing Skills - Raúl Alberto Mora (Asociación Colombiana de Profesores de Ingles, 2016)
Any schoolteacher knows that probably one of the most difficult skills to develop when working with teenagers is writing, no matter the learners' age or proficiency level. It is usually seen as the "boring skill". This presentation aims to show how, by means of Project Work (mainly bridging activities), writing can be dealt with in a more dynamic and entertaining way, while you have a chance to practice other skills simultaneously.